2017
DOI: 10.1007/s10654-017-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Low serum magnesium levels are associated with increased risk of fractures: a long-term prospective cohort study

Abstract: Magnesium, which is an essential trace element that plays a key role in several cellular processes, is a major component of bone; however, its relationship with risk of major bone fractures is uncertain. We aimed to investigate the association of baseline serum magnesium concentrations with risk of incident fractures. We analyzed data on 2245 men aged 42–61 years in the Kuopio Ischemic Heart Disease prospective cohort study, with the assessment of serum magnesium measurements and dietary intakes made at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 43 publications
(56 reference statements)
3
54
0
1
Order By: Relevance
“…It is proposed that measuring the dietary intakes using multiple DRs that are not dependent on memory and has a great specificity in describing foods is a suitable choice to be used as a reference method in validation studies [4,23]. Biochemical markers are also used in epidemiological studies to measure the participants' status regarding specific nutrients or dietary compounds [24,25]. Previous studies indicate high correlations between dietary intake and some biochemical markers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that measuring the dietary intakes using multiple DRs that are not dependent on memory and has a great specificity in describing foods is a suitable choice to be used as a reference method in validation studies [4,23]. Biochemical markers are also used in epidemiological studies to measure the participants' status regarding specific nutrients or dietary compounds [24,25]. Previous studies indicate high correlations between dietary intake and some biochemical markers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Bones loses its quality characteristics according to reduced concentrations of this trace element, which leads to the development of osteoporosis [15]. In a long-term prospective study, which included 2,245 men aged 42 to 61 years, an association of decreased serum magnesium concentration with fractures of the peripheral skeleton was revealed [16]. In a study of chondrocalcinosis in the Chinese population, Zeng et al found that patients with lower serum magnesium levels, even within the normal range, had a higher prevalence of chondrocalcinosis of knee [17].…”
Section: Discussionmentioning
confidence: 99%
“…For matched cohort studies, reporting should include the matching criteria used and the number of participants exposed and unexposed to the hypothesized cause of the outcome; in this case, the methods section also should describe how loss to follow-up was addressed. An example of reporting according to STROBE guidelines for cohort studies is available in Kunutsor et al ’s investigation of the association of baseline serum magnesium concentrations associated with a risk for incident fractures (31). …”
Section: Guidelines For Reporting Public Health Investigation Methodsmentioning
confidence: 99%